A high-speed, high-performance, microfabricated comprehensive two-dimensional gas chromatograph. Issue 9 (28th March 2019) - Whiting, Joshua J.; Myers, Edward; Manginell, Ronald P.; Moorman, Mathew W.; Anderson, John; Fix, Cory S.; Washburn, Cody; Staton, Al; Porter, Daniel; Graf, Darin; Wheeler, David R.; Howell, Stephen; et al.
Abstract : A microfabricated ultrafast GC×GC system, coupled with highly sensitive, low-power NEMS resonators, with handheld form factor for civilian, military, and space applications. Abstract : A small, consumable-free, low-power, ultra-high-speed comprehensive GC×GC system consisting of microfabricated columns, nanoelectromechanical system (NEMS) cantilever resonators for detection, and a valve-based stop-flow modulator is demonstrated. The separation of a highly polar 29-component mixture covering a boiling point range of 46 to 253 °C on a pair of microfabricated columns using a Staiger valve manifold in less than 7 seconds, and just over 4 seconds after the ensemble holdup time is demonstrated with a downstream FID. The analysis time of the second dimension was 160 ms, and peak widths in the second dimension range from 10–60 ms. A peak capacity of just over 300 was calculated for a separation of just over 6 s. Data from a continuous operation testing over 40 days and 20 000 runs of the GC×GC columns with the NEMS resonators using a 4-component test set is presented. The GC×GC-NEMS resonator system generated second-dimension peak widths as narrow as 8 ms with no discernable peak distortion due to under-sampling from the detector.